2018
DOI: 10.1016/j.combustflame.2018.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chemical kinetics on detonation initiating by temperature gradients in methane/air

Abstract: Different simplified and detailed chemical models and their impact on simulations of combustion regimes initiating by the initial temperature gradient in methane/air mixtures are studied. The limits of the regimes of reaction wave propagation depend upon the spontaneous wave speed and the characteristic velocities of the problem. The present study mainly focus to identify conditions required for the development a detonation and to compare the difference between simplified chemical models and detailed chemistry… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…The autoignition front propagation initiated by a hot spot in large or open space has been extensively studied [8,9,14,[17][18][19][20][21][22]. According to the Zel'dovich theory [7] the critical condition for detonation development by the temperature gradient is defined as the condition of coupling of the reaction wave and the pressure wave.…”
Section: Typical Autoignition Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…The autoignition front propagation initiated by a hot spot in large or open space has been extensively studied [8,9,14,[17][18][19][20][21][22]. According to the Zel'dovich theory [7] the critical condition for detonation development by the temperature gradient is defined as the condition of coupling of the reaction wave and the pressure wave.…”
Section: Typical Autoignition Casesmentioning
confidence: 99%
“…This detonation peninsular was widely utilized in the studies on knock and super-knock [3,[10][11][12][13]. Besides, Liberman and co-workers [14,15] studied the combustion regimes induced by the initial temperature gradient. They found that the temperature gradient initiated a detonation predicted by detailed chemical models greatly differs from that predicted using a one-step chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…After the intersection of the spontaneous wave front and the pressure wave, the spontaneous wave evolves into a combustion wave and the pressure wave steepens into the shock wave. The pressure peak becomes large enough and steepens into a detonation wave [7]. This process is defined as a spontaneous initiation.…”
Section: Autoignition and Znd Structure With O3 Additionmentioning
confidence: 99%
“…Liberman & Wang et al [7,8] found that the sustenance of detonation initiated by spontaneous reaction wave is closely related to the ambient temperature and pressure at the end and outside of the temperature gradient. Dai, Qi & Chen et al [9] studied the development of a spontaneous reaction wave in a hot spot with high initial pressure and temperature for large hydrocarbon fuels with low-temperature chemistry which is prone to exhibit the negative temperature coefficient (NTC) phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it was shown that the minimal slope of the temperature gradient required for triggering detonation and other combustion modes obtained in simulations with simplified chemical models, for example a one-step model, is orders of magnitude smaller than those obtained in simulations with a detailed chemical model. Wang et al (2018) and Liberman et al (2019) studied the influence of the chemical reaction model on detonation ignited by a temperature gradient for hydrogen-air and methane-air mixtures. They concluded that the one-step model and other simplified models usually cannot describe correctly the ignition processes.…”
Section: Introductionmentioning
confidence: 99%